2021
DOI: 10.20525/ijrbs.v10i3.1123
|View full text |Cite
|
Sign up to set email alerts
|

The influence of work-family conflict and Islamic work ethics on employee performance

Abstract: This study aims to analyze the influence of work-family conflict and Islamic work ethics on employee performance with work motivation as the mediating variable. The population of this study is female employees of Bank Jateng Syariah. The sampling technique is done using the purposive sampling method. The analysis test tool used in this study is path analysis. The result expected from this study is the analysis of the influence of work-family conflict and Islamic work ethics on employee performance with work mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 31 publications
3
12
0
Order By: Relevance
“…The results of the same study from Sheaffer (2015); Hong et al (2019), work-family conflict has a negative effect on motivation. The results of the research by Widyarini & Muafi (2021), show that work-family conflict has a negative and significant effect on motivation. Yolanda & Purba (2018), found that work-family conflict has a significant influence on motivation.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 97%
See 2 more Smart Citations
“…The results of the same study from Sheaffer (2015); Hong et al (2019), work-family conflict has a negative effect on motivation. The results of the research by Widyarini & Muafi (2021), show that work-family conflict has a negative and significant effect on motivation. Yolanda & Purba (2018), found that work-family conflict has a significant influence on motivation.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 97%
“…Work-family conflict has a negative effect on employee performance and is mediated by motivation which has a very significant role (Widyarini & Muafi, 2021). Riaz et al (2019), found that motivation has a negative and debilitating influence on the relationship between work-family conflict and performance.…”
Section: H2: Work-family Conflict Has a Negative And Significant Effe...mentioning
confidence: 99%
See 1 more Smart Citation
“…In individual ethics, there is a 'personal should', and the person himself makes decisions and rules that obligate him to do or not do the task. In this case, the purpose of righteousness is to improve the life status in the community (Tufail et al 2016;Widyarini & Muafi 2021). Here, we refer to the writings of teachers such as Motahari to present a simple definition of the science of ethics.…”
Section: Islamic Ethicsmentioning
confidence: 99%
“…These findings were confirmed by Liu et al (2020) who reported negative link between WFC and performance of construction professionals in China. Lastly, WFC negatively influenced performance of bankers in Indonesia (Widyarini and Muafi, 2021). Therefore, we have developed our first hypothesis as follows:…”
Section: Literature Background and Hypotheses Development Wfc And Pro...mentioning
confidence: 99%